The Epistemology of Moderate Interpretation: Riwāyah, Ra’yi, and Isyārī and Their Implications for Contemporary Islamic Education - Muhammad Said; Muhammad Farih; Muhammad Alamul Huda (Tilawah: Journal of Al-Qur'an Studies, 2026)
Epistemology of moderate Qur’anic interpretation through the integration of riwāyah, ra’yi, and isyārī approaches and its implications for contemporary Islamic education. The study is motivated by the dynamic development of Qur’anic exegesis which, in modern contexts, faces tendencies toward interpretive extremism, either in rigid textual literalism or overly subjective interpretations that risk undermining the authority of the Qur’anic text. Employing a qualitative library research method, this study analyzes classical and contemporary tafsīr works as well as relevant literature on Islamic education. The findings reveal that riwāyah emphasizes textual authority and transmission, ra’yi highlights rational reasoning and contextual ijtihād, while isyārī enriches the spiritual and ethical dimensions of interpretation. The integration of these three approaches forms a balanced epistemology of moderate tafsīr that harmonizes text, reason, and spirituality. In the context of contemporary Islamic education, this epistemological framework contributes to a shift in educational goals from mere knowledge transmission toward methodological awareness, curriculum development based on tafsīr epistemology, dialogical learning methods, and the cultivation of moderate, tolerant, and inclusive religious attitudes. This study offers a conceptual contribution to the development of Islamic education that remains faithful to Islamic scholarly tradition while addressing contemporary challenges.